Ex-vivo-examination of ultrastructural changes in organotypic retina culture using near-infrared imaging and optical coherence tomography. (June 2016) - Schnichels, Sven; Dorfi, Tanja; Schultheiss, Maximilian; Arango-Gonzalez, Blanca; Bartz-Schmidt, Karl-Ulrich; Januschowski, Kai; Spitzer, Martin S.; Ziemssen, Focke
Abstract: Optical coherence tomography (OCT) dramatically changed the way of diagnostic assessment in retinal diseases during the last years. Using this technique in-vivo in-depth analysis of the retina and its layers is possible. Since animal research is changing by intrinsic and extrinsic pressure to animal-( in-vivo )-free methods, we adapted OCT-measurements to organotypic cultures. An easy to use protocol was generated to assess standardized OCT assessments in organotypic culture. First, two custom-made devices need to be made to change any commercially available OCT for examinations in humans into a device allowing ex-vivo analyses of organotypic culture. The modification is feasible within seconds. After OCT measurement of the ex-vivo tissues, quantitative evaluation of the retinas were performed via ImageJ software. OCT pictures of ex-vivo retinas were obtained for time periods of seven days and the thickness of retinal tissue was evaluated. The reproducibility of the pictures and measurements was very high (SD < 15%). In conclusion, an easy to use protocol for the investigation of different effects on retinal cultures with commercially available OCT devices was successfully established. Highlights: OCT-measurements were adapted to organotypic cultures. in-vitro in-depth analysis of the retina and its layers are possible. an easy to use protocol with commercially available OCT devices is given. Animal experiments can be reduced with this technique.